Breaking the mold: An evaluation of the EU-New Zealand Free Trade Agreement as a new "gold standard" for Trade and Sustainable Development chapters - Ulrike Carrillo (Martin-Luther-Universität Halle-Wittenberg, Institut für Wirtschaftsrecht, Forschungsstelle für Transnationales Wirtschaftsrecht, 2024)
This paper evaluates the Trade and Sustainable Development (TSD) Chapter of the EU-New Zealand Free Trade Agreement (FTA) and its potential to establish a new standard for sustainability provisions in EU trade agreements. The paper explores the political and economic context of the EU-NZ FTA and the developments leading up to the EU's revised approach to TSD Chapters. The analysis focuses, in particular, on the substantial and institutional provisions within the TSD Chapter, with a focus on their enforceability under the agreement's general dispute settlement mechanism. It draws parallels to previous EU FTAs and concludes by forecasting the potential impact of the EU-NZ FTA on future EU trade deals.
Keywords: 340; Freihandelsabkommen; Außenhandel; Nachhaltige Entwicklung; Neuseeland; EU-Staaten; Freihandelsabkommen; Außenhandel; Nachhaltige Entwicklung; Neuseeland; EU-Staaten